Corrosion Behavior of a Nickel-Base Dental Casting Alloy in Artificial Saliva Studied by Weight Loss and Polarization Techniques - Elnaz Moslehifard; Mahsa Moslehifard; Sanaz Ghasemzadeh; Farzad Nasirpouri (Tehran University of Medical Sciences, 2019)
Objectives: Nickel-chromium (Ni-Cr) base dental alloys with desirable properties have been employed in prosthodontics for years. Corrosion behavior of a Ni-Cr base alloy in artificial saliva with different pH values is determined in this work. Materials and Methods: Corrosion behavior of Ni-Cr alloy was studied using weight loss described by corrosion rate (CR) in mils per year (mpy) and potentiodynamic polarization described by corrosion potential (CP) in mV and current density (CD) in mA/cm2 in artificial saliva with different pH. Surface morphology was studied using scanning electron microscopy (SEM). Statistical difference was assessed using one-way ANOVA and post-hoc Tukey's honestly significant difference (HSD) test with a difference significance of 95%. Results: In weight loss method, CR was 71.95±3.40, 17.26±1.03, 8.92±0.35, and 6.93±0.54 mpy at pH values of 2.5, 5, 7, and 9, respectively. CR obtained at pH of 2.5 was significantly different than that in other groups, but those obtained at pH of 5, 7, and 9 were not significantly different. In the polarization method, CP values were significantly different. CD measured at pH of 2.5 and 5 was significantly different than the rest of pH values (P<0.05). CRs at pH of 7 and 9 were not significantly different. SEM exhibited the formation of preferential sites of corrosion attacks influenced by pH. Conclusions: Both techniques revealed consistent results. Corrosion resistance increases as pH increases towards less acidic conditions. In more acidic saliva, .....